EFFECT OF CALCIUM HYDROXYAPATITE AND HYALURONIC ACID INJECTIONS ON INFLAMMATION MARKERS OF PERIODONT TISSUE - Larkina, S.A.; Seletskaya, А.V.; Makarenko, O.А.; Schneider, S.A. (World of Medicine and Biology, 2021)
The purpose of the study was to evaluate the anti-inflammatory properties of injections of calcium hydroxyapatite (CaNA) of different concentrations and hyaluronic acid on the condition of periodontal tissues in rats with experimental periodontitis. A subacute experiment was performed using a model of alimentary-induced periodontitis. Experimental studies have shown the ability of calcium hydroxyapatite in combination with hyaluronic acid to inhibit the activity of destructive enzymes and increase the activity of osteoblast markers in the bone tissue of the jaws of rats with periodontitis along with reducing markers of inflammation in the gums of animals with periodontitis. Injections of calcium hydroxyapatite with hyaluronic acid have a significant anti-inflammatory effect on the soft tissues of the periodontium, reducing the homogenates of the gums of rats with periodontitis malondialdehyde level by 24.6–40.3 %, acid phosphatase activity by 25.3–38.3 %, elastase activity by 23.5–29.8 %.
Keywords: experimental periodontitis; rats’; bone tissue; hyaluronic acid; calcium hydroxyapatite; periodontitis; subgingival injections